The effect of inflation, exchange rate and gold on the Indonesian JCI: non-linear approach / Ilham Maulana and Bambang Haryadi - Maulana, Ilham; Haryadi, Bambang (Universiti Teknologi MARA, Cawangan Melaka, 2022)
Predicting the stock market is very difficult to do, because the stock market has a high complexity, but predicting the stock market is a necessity because it directly relates to the profits of the actors involved in the stock market. This study tries to examine the determinant factors that can affect stock market conditions. By using the level of Inflation, Exchange, and Gold as predictors of the stock market in Indonesia. Using data from January 2005 – December 2020, the researcher then analyzed the data using the Warppls 7.0 application in order to be able to analyze it non-linearly, because the complexity of the stock market makes it very possible that the analysis carried out must be in a non-linear form in order to gain broader insight into the factors that affect the market. Our finding are that gold and exchange rate are signicant, whereas the inflation is not toward Indonesian JCI level.